Pta1, a Component of Yeast CF II, Is Required for Both Cleavage and Poly(A) Addition of mRNA Precursor - Zhao, Jing (American Society for Microbiology, 1999)
CF II, a factor required for cleavage of the 3′ ends of mRNA precursor in Saccharomyces cerevisiae, has been shown to contain four polypeptides. The three largest subunits, Cft1/Yhh1, Cft2/Ydh1, and Brr5/Ysh1, are homologs of the three largest subunits of mammalian cleavage-polyadenylation specificity factor (CPSF), an activity needed for both cleavage and poly(A) addition. In this report, we show by protein sequencing and immunoreactivity that the fourth subunit of CF II is Pta1, an essential 90-kDa protein originally implicated in tRNA splicing. Yth1, the yeast homolog of the CPSF 30-kDa subunit, is not detected in this complex. Extracts prepared from pta1 mutant strains are impaired in the cleavage and the poly(A) addition of both GAL7 and CYC1 substrates and exhibit little processing activity even after prolonged incubation. However, activity is efficiently rescued by the addition of purified CF II to the defective extracts. Extract from a strain with a mutation in the CF IA subunit Rna14 also restored processing, but extract from a brr5-1 strain did not. The amounts of Pta1 and other CF II subunits are reduced in pta1 strains, suggesting that levels of the subunits may be coordinately regulated. Coimmunoprecipitation experiments indicate that the CF II in extract can be found in a stable complex containing Pap1, CF II, and the Fip1 and Yth1 subunits of polyadenylation factor I. While purified CF II does not appear to retain the association with these other factors, this larger complex may be the form recruited onto pre-mRNA in vivo. The involvement of Pta1 in both steps of mRNA 3′-end formation supports the conclusion that CF II is the functional homolog of CPSF.